The Effect of Terrorism on Tourism Development in Nigeria: A Note (2017)
This article investigated the tourism–terrorism nexus in Nigeria using quarterly time series data within a vector autoregression analytical framework. Unlike extant studies, we gauge the influence of terrorism shocks on the tourism sector specifically on the one hand and broadly the response of some key macroeconomic variables on the other hand. Several interesting results ensued. To sum up these findings, we found a negative response of tourism revenues to terrorist incidents over the long haul as well as adverse effects on other key macroeconomic variables. Therefore, government policies to revamp the ailing economy should be complemented with well-tailored counterterrorism approaches for effectiveness.